2023
DOI: 10.3201/eid2903.221245
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia thailandensis Isolated from the Environment, United States

Abstract: Burkholderia thailandensis , an opportunistic pathogen found in the environment, is a bacterium closely related to B. pseudomallei , the cause of melioidosis. Human B. thailandensis infections are uncommon. We isolated B. thailandensis from water in Texas and Puerto Rico and soil in Mississippi in the United States, demonstrating a potential public health risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…12 ), suggesting that these overlapping bacteria were more reliable. It should be noted that studies have suggested that the characteristic bacteria we found, such as Burkholderia 27 and Ralstonia 28 , are easy to grow and have a high risk of waterborne genera and oral contaminants, although studies have also reported the presence of these bacteria in the oral cavity 29 , 30 . These disputes may be related to the molecular definition of the species, or to this particular population and their environment/habits, besides the possibility of contamination.…”
Section: Discussionmentioning
confidence: 72%
“…12 ), suggesting that these overlapping bacteria were more reliable. It should be noted that studies have suggested that the characteristic bacteria we found, such as Burkholderia 27 and Ralstonia 28 , are easy to grow and have a high risk of waterborne genera and oral contaminants, although studies have also reported the presence of these bacteria in the oral cavity 29 , 30 . These disputes may be related to the molecular definition of the species, or to this particular population and their environment/habits, besides the possibility of contamination.…”
Section: Discussionmentioning
confidence: 72%
“…In regions where the disease is/was not endemic, like the continental US, physicians are not familiar with disease symptomatology thus melioidosis may be given little consideration during initial diagnoses. Further, automated systems that perform bacterial identification may misidentify B. pseudomallei [14]. Therefore, accurate identification of melioidosis cases should be urged among healthcare providers, including the use of culture methods which are still considered the gold standard for the diagnosis of melioidosis which provides conclusive evidence for the presence of the pathogen.…”
Section: Disease Awareness and Diagnosismentioning
confidence: 99%
“…Further, automated systems that perform bacterial identification may misidentify B . pseudomallei [ 14 ]. Therefore, accurate identification of melioidosis cases should be urged among healthcare providers, including the use of culture methods which are still considered the gold standard for the diagnosis of melioidosis which provides conclusive evidence for the presence of the pathogen.…”
mentioning
confidence: 99%
“…Burkholderia thailandensis, an opportunistic pathogen which only rarely causes human infections, is closely related to B. pseudomallei, and is similarly found in the environment. B. thailandensis has been isolated from water in Texas and Puerto Rico and from the soil in Mississippi, demonstrating an environment suitable for Burkholderia species colonization in parts of the Southern United States and in outlying territories (Hall et al, 2023). Interestingly, climate change appears to play a role in the increased range and magnitude of infections by these bacteria (Gassiep et al, 2023).…”
Section: Introductionmentioning
confidence: 99%